Evaluation techniques of hydrogen permeation in sealing rubber materials - Jae Kap Jung (Elsevier, 2021)
Three techniques for determining the hydrogen permeation properties of rubber samples were developed based on the volumetric and gravimetric measurements of released H2 gas after sample decompression. These methods include gas chromatography (GC) by thermal desorption analysis (TDA), volumetric collection (VC) measurement of hydrogen by graduated cylinder and gravimetric (GM) measurement by electronic balance. By measuring the released hydrogen against elapsed time after the decompression of pressure, the charging amount (C0) and diffusivity (D) were obtained with the developed diffusion analysis program. From these values, the solubility (S) and permeability (P) of polymers were evaluated through the relations of Henry's law andP=SD, respectively. The developed techniques were applied to three kinds of spherically shaped sealing rubber materials. D, S and P were analyzed as a function of pressure. The transport behaviors obtained in the three methods are discussed and compared with the characteristics of each measuring technique. The correlations between transport parameters and carbon black filler or density are discussed.